Объяснение:
x³ + x²y - xy² + x²y + xy² - y³ = x³ + 2x²y - y³
n³ - n²p +np²- n²p + np² - p³ = n³ - 2n²p + 2np² - p³
a³ - a²x - ax² + a²x - ax² - x³ = a³ - 2ax² - x³
b³ - b²c -bc² - b²c + bc² + c³ = b³ - 2b²c + c³
1)(х^2 +ху-у^2) (х+у) =
=Х^3+х^2 у+х^2 у+xy^2 -ху^2 -у^3=
Сокращаем +ху^2 и - ху^2
=х^3+2х^2у-у^3
2)(n^2 - np-p^2) (n-p) =
=n^3-n^2 p-n^2 p+np^2+np^2 - p^3=
=n^3-2n^2 p-2np^2 - p^3
3)(a-x)(a^2 - ax-x^3)=
=a^3-a^2 x-ax^3-a^2 x+ax^2 +x^4=
=a^3-2a^2 x-ax^3+ax^2 +x^4
4)(b-c)(b^2 - bc-c^2) =
=b^3-b^2 c-bc^2 - b^2 c+bc^2 +c^3=
сокращаем - bc^2 и +bc^2
=b^3-2b^2 c+c^3
этот ^означает степень
Объяснение:
x³ + x²y - xy² + x²y + xy² - y³ = x³ + 2x²y - y³
n³ - n²p +np²- n²p + np² - p³ = n³ - 2n²p + 2np² - p³
a³ - a²x - ax² + a²x - ax² - x³ = a³ - 2ax² - x³
b³ - b²c -bc² - b²c + bc² + c³ = b³ - 2b²c + c³
1)(х^2 +ху-у^2) (х+у) =
=Х^3+х^2 у+х^2 у+xy^2 -ху^2 -у^3=
Сокращаем +ху^2 и - ху^2
=х^3+2х^2у-у^3
2)(n^2 - np-p^2) (n-p) =
=n^3-n^2 p-n^2 p+np^2+np^2 - p^3=
=n^3-2n^2 p-2np^2 - p^3
3)(a-x)(a^2 - ax-x^3)=
=a^3-a^2 x-ax^3-a^2 x+ax^2 +x^4=
=a^3-2a^2 x-ax^3+ax^2 +x^4
4)(b-c)(b^2 - bc-c^2) =
=b^3-b^2 c-bc^2 - b^2 c+bc^2 +c^3=
сокращаем - bc^2 и +bc^2
=b^3-2b^2 c+c^3
Объяснение:
этот ^означает степень